Effectiveness of Using Bioball and Pumice Biofiltration on Water Quality in Recirculating Tilapia Cultivation System - Rizky Kusma Pratiwi; Andi Masriah; Zakiyyah Nur Inayah; Vina Nur Nadiro; Vika Maulidiyah; Muhamad Dwi Cahya; Admiral Amin Supit; Muhammad Zidny Sahlan; Beby Adi Surya Saputra; Stevanus Bondan Wijaya (Jurnal Sains dan Teknologi Perikanan, 2026)
The use of simple filter media can reduce organic waste materials in Nile tilapia aquaculture systems. The performance of biofilters is strongly influenced by the type of media used, depending on their characteristics in supporting biofilm formation. This study aimed to analyze the effectiveness of bioball and pumice as biofilter media on water quality and the growth performance of Nile tilapia (Oreochromis niloticus) in a recirculating aquaculture system. The research was conducted from October to November 2024 at the Integrated Farming Laboratory, PSDKU Universitas Brawijaya Kediri, using an experimental method. Two treatments were applied, namely bioball (P1) and pumice (P2), with observations on water quality parameters including temperature, pH, dissolved oxygen (DO), Total Organic Matter (TOM), alkalinity, ammonia, nitrate, and phosphate, as well as fish growth parameters including absolute growth, specific growth rate (SGR), and survival rate (SR). Data were analyzed using the Independent Sample T-Test, while alkalinity, absolute growth, and survival rate were analyzed using the non-parametric Mann–Whitney U test. The results showed that the use of biofilter media did not have a significant effect (p>0.05) on all water quality parameters, but showed a significant difference in absolute growth. Pumice media demonstrated better performance in increasing DO (5.6–10.3 mg/L) and reducing organic matter with a removal efficiency of 33–70% and ammonia up to 94%. In terms of growth performance, the pumice treatment produced higher values of absolute growth (2.52 ± 0.26 g), SGR (2.53 ± 0.18%/day), and SR (86.7 ± 4.7%) compared to bioball. Therefore, pumice has the potential to be recommended as a promising biofilter medium for improving water quality and growth performance of Nile tilapia in recirculating aquaculture systems.